2003
DOI: 10.1002/jid.973
|View full text |Cite
|
Sign up to set email alerts
|

Fooling the eye of the beholder: deceptive status signalling among the poor in developing countries

Abstract: Poor consumers in the developing world use a variety of status signalling devices that rely on deception of the observer. A frequently used deceptive strategy is the consumption of counterfeit instead of original status-intensive goods, mainly cheap copies of expensive brand-name goods from developed countries. The choice for such deceptive modes of conspicuous consumption is analysed within a product characteristics approach as developed by Lancaster and compared with non-deceptive alternatives. Under the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 21 publications
2
50
0
4
Order By: Relevance
“…This is supported by this study, which shows that poverty was identified as a major contributor to consumption of counterfeit products, which accounted for 5.024% of total variance. Though this supports the finding of Kempen (2003) and Tom, Garibaldi, Zeng and Pilcher (1998), more studies ought to be done because on contrary the focused population in this study was from middle class.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
See 1 more Smart Citation
“…This is supported by this study, which shows that poverty was identified as a major contributor to consumption of counterfeit products, which accounted for 5.024% of total variance. Though this supports the finding of Kempen (2003) and Tom, Garibaldi, Zeng and Pilcher (1998), more studies ought to be done because on contrary the focused population in this study was from middle class.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
“…Only Kempen (2003), who included this variable and found that there existed low level of after purchase disappointment. This study will seek to contribute to this area as well, by seeking to understand how the experience of those who have purchased counterfeit products impact on their future or next purchase.…”
Section: Forces Driving Counterfeit Tradementioning
confidence: 99%
“…This view supports the work of Van Kempen (2003) and contradicts the view of others (i.e., Jiang and Cova, 2012), who state that today many counterfeits have the same quality and even better durability than the genuine ones. Moreover, some respondents expressed their concerns about whether the genuine luxury brands that are sold in the regular stores or department stores are not counterfeits.…”
Section: Counterfeiting As a Phenomenon-knowledge And Perceptionsmentioning
confidence: 42%
“…Very much of the squalor and discomfort will be endured before the last trinket or the last pretence of pecuniary decency is put away." For further discussion of conspicuous consumption by the poor see Luuk van Kempen (2003). not so severe, there is less pressure to compete and the individual with the lowest income behaves as though she were completely indifferent to status concerns and spends the cooperative amount.…”
mentioning
confidence: 99%